Phase II Trial of Pembrolizumab Plus Gemcitabine, Vinorelbine, and Liposomal Doxorubicin as Second-Line Therapy for Relapsed or Refractory Classical Hodgkin Lymphoma. Issue 28 (1st October 2021) - Moskowitz, Alison J.; Shah, Gunjan; Schöder, Heiko; Ganesan, Nivetha; Drill, Esther; Hancock, Helen; Davey, Theresa; Perez, Leslie; Ryu, Sunyoung; Sohail, Samia; Santarosa, Alayna; Galasso, Natasha; et al.
Abstract : PURPOSE: We conducted a phase II study evaluating pembrolizumab plus gemcitabine, vinorelbine, and liposomal doxorubicin (pembro-GVD) as second-line therapy for relapsed or refractory (rel/ref) classical Hodgkin lymphoma (cHL) (ClinicalTrials.gov identifier: NCT03618550 ). METHODS: Transplant eligible patients with rel/ref cHL following first-line therapy were treated with two to four cycles of pembrolizumab (200 mg intravenous [IV], day 1), gemcitabine (1, 000 mg/m 2 IV, days 1 and 8), vinorelbine (20 mg/m 2 IV, days 1 and 8), and liposomal doxorubicin (15 mg/m 2, days 1 and 8), given on 21-day cycles. The primary end point was complete response (CR) following up to four cycles of pembro-GVD. Patients who achieved CR by labeled fluorodeoxyglucose-positron emission tomography (Deauville ≤ 3) after two or four cycles proceeded to high-dose therapy and autologous hematopoietic cell transplantation (HDT/AHCT). HDT/AHCT was carried out according to institutional standards, and brentuximab vedotin maintenance was allowed following HDT/AHCT. RESULTS: Of 39 patients enrolled, 41% had primary ref disease and 38% relapsed within 1 year of frontline treatment. 31 patients received two cycles of pembro-GVD, and eight received four cycles. Most adverse events were grade 1 or two, whereas few were grade 3 and included transaminitis (n = 4), neutropenia (n = 4), mucositis (n = 2), thyroiditis (n = 1), and rash (n = 1). Of 38 evaluable patients, overall and CR rates after pembro-GVD were 100% and 95%, respectively. Thirty-six (95%) patients proceeded to HDT/AHCT, two received pre-HDT/AHCT involved site radiation, and 13 (33%) received post-HDT/AHCT brentuximab vedotin maintenance. All 36 transplanted patients are in remission at a median post-transplant follow-up of 13.5 months (range: 2.66-27.06 months). CONCLUSION: Second-line therapy with pembro-GVD is a highly effective and well-tolerated regimen that can efficiently bridge patients with rel/ref cHL to HDT/AHCT.